Sistem Informasi Rekomendasi Pemesanan Obat Dengan Metode Reorder Point Di Apotek Tunggilis - Rohma Umaysaroh, Nur; Jaenudin, Jejen; Rachmawati, Fitria (Jurnal Etnik: Ekonomi-Teknik, 2023)
In ensuring the quality of pharmaceutical services, proper control of pharmaceutical supplies must be carried out. One of them is to prevent or minimize the occurrence of vacancies in pharmaceutical supplies needed. Problems that occur at the Tunggilis Pharmacy include the inaccuracy of officers in checking drug stock, delays in ordering drugs to distributors, inaccurate procurement planning resulting in conditions where inventory is smaller or larger than needed. The process of ordering drugs that is done conventionally will take a lot of time and energy so that an information system is needed that can provide information according to the items needed and when the time is right so that pharmacies can order drugs again. One of the effective systems is the recommendation system. In recommending automatic drug orders, it is processed with the help of the Reorder Point (ROP) method as a form of convenience in calculating the timeliness of ordering drugs to maintain drug availability at the Tunggilis Pharmacy. The system development in this study refers to the SDLC (System Development Life Cycle) method with the waterfall model. The results of this study based on system testing that has been carried out using the Black Box method, it can be concluded that this system can be used and can facilitate users in managing drug availability.